Review and Outlook of China Non-Road Diesel Mobile Machinery Emission Standards : Stricter emissions standards for better air quality in China. Issue 1 (1st January 2020) - Huanxing, Cui; Gang, Li; Ying, Yuan; Liang, Ji; Shunli, Liu
China has continuously upgraded the emission standards for non-road diesel mobile machinery since they were first issued in 2007. This paper reviews the Chinese non-road diesel mobile machinery emission standards, analyses the change in the environmental situation and management policy and puts forward some principles and suggestions for developing emission standards for non-road mobile machinery in the future. It will have a positive effect on improving the theory and methods for developing mobile source emission standards, as well as boosting the level of environmental management and emission control in China.